PENGRAJIN BATIK SASAMBO DI DESA REMBITAN DALAM MEMBENTUK WISATA BERBASIS BATIK SASAMBO - Sukarni, Sri; Windhari, Gusti Ayu Esty (Lumbung Inovasi: Jurnal Pengabdian kepada Masyarakat, 2017)
Sasambo Rembitan Sasak (SRS) has opportunity to develop new business besidesproduce batik Sasambo. The new business is Batik Sasambo tour. Problems faced by the SRS to build Batik Sasambo tour concerned with man resources and information media such as 1). Description about batik Sasambo in English is not available; 2). A few of the craftsmen can speak English. This community service activity aimed to: 1) give information about batik Sasambo produced by Sasambo Rembitan Sasak in English through booklet and brochure; 2) increase craftsmen and staffs’ ability in English; 3) prepare the establishment of Batik Sasambo Tour. The community service is done in three steps are establishment, partner participation and evaluation. Establishment is done through English training, made booklet and brochure in English and initial development of Batik Sasambo tour. Partner participation is active during the implementation the program. Evaluation and sustainability is done after the program and both community service team and partners together not only to prepare SRS to build Batik Sasambo tour but also to be a location for research and working practice. Result of community service showed 1) craftsmen’s performance in English is good; 2) booklet and brochure about Batik Sasambo are provided; 3) preparation to build Batik Sasambo tour.